Features of land use optimization of water protection zones and coastal protective strips in Kyiv by the method of land management - Kravchuk, T. (Land Management, Cadastre and Land Monitoring, 2021)
Abstract. In the process of working on the article, the author considered the issue of establishing and ensuring compliance with the land use regime of water protection zones and coastal protection strips (on the example of the city of Kyiv). The urgency of considering this issue lies in the importance of optimizing land use as one of the most important tools to protect water bodies from technogenic and anthropogenic impacts and, in general, to improve the water-ecological situation of the hydrological regime. From which the purpose of the work follows, namely, to study the features of optimization of land use of water protection zones and coastal protection zones in Kyiv by the method of land management for the environmental safety of the city’s population and public welfare in general. As a result of the research process, the theoretical basis was formed by scientific works related to the essence of the task, as well as legislative and regulatory legal acts of Ukraine on land use regulation. The information and statistical base was an extract from the scheme of planning restrictions of the General Plan of Kyiv and data of the State Service of Ukraine on Geodesy, Mapping and Cadastre, the State Statistics Service of Ukraine. As a result of research, it was revealed that according to the legislation on the lands of cities and urban-type settlements, the size of the water protection zone, as well as the coastal protection zone, is established according to existing at the time of installation of a water protection zone concrete building conditions. Nevertheless, the example of the city of Kyiv shows that such information may be missing. The author describes the problematic issues of the land management process of works on establishing the boundaries of water protection zones and coastal protection zones and restrictions on the use of land and other natural resources. Expertly determined the approximate possible area, taking into account the specific building conditions and possible flooding at the maximum flood water level. The model of optimization of land use of the territorial community by means of establishment of restrictions in use of the earths and other natural resources occupied by water objects is proposed. At the same time, the model combines technological, instructional and administrative tasks of land use optimization. In addition, the optimality criteria and restrictions on the use of these criteria proposed in the model, which make it possible to unambiguously determine the location of the boundaries of water bodies and restrictions on the use of lands and other natural resources, taking into account the interests of land users and legislation. Keywords: land use optimization, water protection zones, coastal protection strips, land management process